The fluid-structure interaction of a spring-mounted cantilevered-free flexible plate in a uniform flow - Howell, Richard; Lucey, Anthony (Ex Ordo, 2012)
We study a new fundamental system comprising a cantilevered thin flexible plate aligned with a uniform flow in which its upstream end is attached to a spring mass system. This allows the entire system to oscillate perpendicularly to the flow direction as a result of the mounting’s dynamic interaction with the flow-induced oscillations of the flexible plate. The long-term goal of the study is the development of an energy harvesting system whereby the reciprocating motion of the support system can be tapped for energy production. Here we formulate and deploy a hybrid of theoretical and computational models for the system and map out its linear stability characteristics. Compared to a fixed cantilever, the introduction of the dynamic support system yields lower flutter-onset flow speeds and a reduction of the order of the mode that yields the critical flow speed, effects that are desirable for energy harvesting.